2012
DOI: 10.1149/2.020209jes
|View full text |Cite
|
Sign up to set email alerts
|

Leveler Effect and Oscillatory Behavior during Copper Electroplating

Abstract: The electrochemical behavior of levelers was studied and compared for two commercial Cu plating chemistries in an effort to correlate the electrochemical behaviors with their impacts on bottom-up filling, impurity incorporation, and grain structures. While a strong complexing between leveler and accelerator resulted in a leveler-sensitive bottom-up filling rate and low impurity level in the deposit, a traditional non-interacting leveler showed little impact on the filling performance and yielded a high impurit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 16 publications
4
38
0
Order By: Relevance
“…As imilar effect has been reported by Huang et al for the incorporation of commercial leveler additives. [12] At otal number of 15 maximai nt he SIMS depth profiles (see panel Ci nF igure 3) correlate with the same number of potential oscillations in the potential/time transient curve,a tl east for the low-frequency oscillation. It is, however,n ot possible to precisely reproduce the absoluten umber of maximaa nd minimao ft he SIMS depth profile from the high-frequency deposition process.…”
Section: Film Characterization By Sims Depth Profilingmentioning
confidence: 90%
See 1 more Smart Citation
“…As imilar effect has been reported by Huang et al for the incorporation of commercial leveler additives. [12] At otal number of 15 maximai nt he SIMS depth profiles (see panel Ci nF igure 3) correlate with the same number of potential oscillations in the potential/time transient curve,a tl east for the low-frequency oscillation. It is, however,n ot possible to precisely reproduce the absoluten umber of maximaa nd minimao ft he SIMS depth profile from the high-frequency deposition process.…”
Section: Film Characterization By Sims Depth Profilingmentioning
confidence: 90%
“…Huang et al reported av ery similarn onlinear instability in galvanostaticC ue lectroplating in the presence of ac ommercial leveler additive used for Damascene applications. [12] The current paper is organized as follows. In the first part, we present two oscillatory Cu platinge xperiments, representing two extremes in the frequency of the potential oscillation [low-frequency (L) and high-frequency (H) limits].T he electrochemicalo scillations are then discussed on the basis of their respective SIMS depth profiles.…”
Section: Introductionmentioning
confidence: 99%
“…The second possible way of changing the super filling by the leveler is that the presence of leveler in the bulk solution can change the potential bias applied to the wafer, or the potential transients acquired during the first experiment. 33 However, this leveler effect is only present in a longer time scale, typically after about 20 seconds, 33 as compared with the filling time, typically within 5 seconds. The potential response within a few seconds is independent of the presence of leveler and is only determined by the suppressor and accelerator.…”
Section: Resultsmentioning
confidence: 99%
“…Ni was plated with the same chemistry and condition as described above for Ni silicide formation. A typical damascene plating solution 19 for interconnect fabrication was used to plate the Cu grid. While studies with other chemistries showed the damascene plating solution was not necessary, the studies presented in this paper used a same damascene Cu chemistry.…”
Section: Methodsmentioning
confidence: 99%